MOTIVASI REMAJA DI SMA NEGERI 1 MENGWI MENGGUNAKAN APLIKASI LINE SEBAGAI MEDIA KOMUNIKASI - Adi Pratiwi, Ni Komang; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2018), 2018)
ABSTRACT                                                     LINE is a free instant messaging application that can be used to send text messages, send photos, videos, voice messages, etc. This research focused on Motivation of Application Use for Communication Media. The research aim is to describe motives students in SMA 1 Mengwi while using LINE as communication medium. This research used Uses and Gratification theory with a Study Of McQuail’s Media Consuming Motives. Descriptive Quantitative method is usedand data were collected by Question are with 308 students in total. This study found four motives such as, Information Motive, there were Personal Identity Motive, Social Interaction Motive, and Entertainment Motive. Furthermore, Information Motive was the highest in percentage and the Personal Identity Motive was the lowest. Keyword: Instant Messaging, LINE, Motives